Performing the Bible in the Korean Context: Korean Ways of Reading, Singing, and Dramatizing the Scriptures - Sung Uk Lim (Religions, 2018)
The present study explores the performative nature of the Bible as a sacred text in the Korean context. Drawing on the theory of scriptural performance advocated by James W. Watts, I investigate its character as words and contents. First, I delve into the scriptural performance of thoroughly reading (and listening to) the Bible at the level of words. Second, I scrutinize the scriptural performance of singing and dramatizing the Bible at the level of contents. The specific context of South Korea—whether religious, cultural, or social—alerts us to the performed transformation of the semantic range of the long-standing Christian tradition. Given the cultural differences between Western and Eastern Christianity, I contend that the adaptation of Christianity to Korean soil renders the performative dimension of the scriptures all the more semantic. In other words, the Korean ways of performing the Bible are essentially deeply rooted in those of signifying it. In the long term, Christianity turns out to be such a global religion that it provokes a more complex analysis of its scriptural performance in its widely differing range of semantics.